CEGAH PENULARAN PENYAKIT HEPATITIS B PADA IBU HAMIL MELALUI PENINGKATAN PENGETAHUAN, DETEKSI DINI DAN PHBS DI WILAYAH PUSKESMAS SUNGAI TABUK I KABUPATEN BANJAR: CEGAH PENULARAN HEPATITIS B PADA SANTRI MELALUI PENINGKATAN PENGETAHUAN, DITEKSI DINI DAN PHBS DI PESANTREN RAUDHATUN NASYI’IN SUNGAI BESAR BANJARBARU - Wahdah Norsiah; Neni Oktiyani; Tini Elyn Herlina (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2026)
Transmission of Hepatitis B Virus (HBV) occurs through two main routes: vertical transmission, where an infected mother passes the virus to her baby during childbirth, and horizontal transmission, where an individual with HBV transmits the virus to others through sexual contact, blood transfusion, or the shared use of personal items such as combs, razors, blankets, and eating utensils contaminated with the virus. High-risk groups for HBV transmission include inmates in correctional facilities, family members or household contacts of infected individuals, residents of orphanages, and those living in boarding-type educational institutions such as Islamic boarding schools (pondok pesantren) and other similar settings. The objective of this community service activity was to increase knowledge, conduct HBV and Anti-HBs screening, and promote clean and healthy living behavior (PHBS) among the students (santri) at Pondok Pesantren Raudhatun Nasyi’in, Sungai Besar, Banjarbaru. The results of the screening showed that all 30 students (100%) tested negative for HBsAg, while 1 student (3%) was positive for Anti-HBs and 29 students (97%) were negative. The level of knowledge before the educational intervention was poor in 20%, fair in 33%, and good in 47% of participants. After the educational session, the results improved significantly, with 7% fair and 93% good levels of knowledge. Implementation of clean and healthy living behavior (PHBS) indicators showed 95% for personal hygiene, 97% for environmental cleanliness, and 95% for the use of available facilities. In conclusion, no students were found to be infected with Hepatitis B. There was a significant improvement in knowledge, attitudes, and skills among the students in practicing clean and healthy living behavior.